Pendidikan Islam dan Ide Kreatif dalam Memulai Usaha - Nurhasanah; Nini Aryani; Agustiar (MGMP PAI SMP BINTAN, 2025)
Entrepreneurship is the skill of creating added value by managing resources in a creative and innovative way. Starting a business as an entrepreneur involves focusing on three key aspects: the business idea, market opportunities, and competition. A business idea forms the foundation of any entrepreneurial activity and can stem from personal interests, awareness of everyday problems, or market trends. Business opportunities are then evaluated by analyzing consumer needs, market segmentation, technological trends, and socio-economic conditions. To thrive in a competitive market, entrepreneurs must develop a competitive edge, conduct thorough market research, and apply effective innovation and marketing strategies. This article takes a structured and analytical approach to offer practical guidance for aspiring entrepreneurs in building sustainable and market-responsive businesses.